Regulated Proteolysis in Vibrio cholerae Allowing Rapid Adaptation to Stress Conditions - Pennetzdorfer, Nina; Lembke, Mareike; Pressler, Katharina; Matson, Jyl S.; Reidl, Joachim; Schild, Stefan (Frontiers in Cellular and Infection Microbiology, 2019)
The lifecycle of the causative agent of the severe secretory diarrheal disease cholera, Vibrio cholerae, is characterized by the transition between two dissimilar habitats, i.e., as a natural inhabitant of aquatic ecosystems and as a pathogen in the human gastrointestinal tract. Vibrio cholerae faces diverse stressors along its lifecycle, which require effective adaptation mechanisms to facilitate the survival fitness. Not surprisingly, the pathogen's transcriptome undergoes global changes during the different stages of the lifecycle. Moreover, recent evidence indicates that several of the transcription factors (i.e., ToxR, TcpP, and ToxT) and alternative sigma factors (i.e., FliA, RpoS, and RpoE) involved in transcriptional regulations along the lifecycle are controlled by regulated proteolysis. This post-translational control ensures a fast strategy by the pathogen to control cellular checkpoints and thereby rapidly respond to changing conditions. In this review, we discuss selected targets for regulated proteolysis activated by various stressors, which represent a key feature for fast adaptation of V. cholerae.